2014
DOI: 10.1175/jcli-d-13-00273.1
|View full text |Cite
|
Sign up to set email alerts
|

North American Climate in CMIP5 Experiments: Part III: Assessment of Twenty-First-Century Projections*

Abstract: In part III of a three-part study on North American climate in phase 5 of the Coupled Model Intercomparison Project (CMIP5) models, the authors examine projections of twenty-first-century climate in the representative concentration pathway 8.5 (RCP8.5) emission experiments. This paper summarizes and synthesizes results from several coordinated studies by the authors. Aspects of North American climate change that are examined include changes in continental-scale temperature and the hydrologic cycle, extremes ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
169
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 246 publications
(193 citation statements)
references
References 124 publications
21
169
3
Order By: Relevance
“…Although barely significant (see the limited extent of the stippling), there is general drying in Mexico and Texas, extending into the southwest US, and more positive anomalies in the eastern gulf and Florida. The pattern of yearly anomalies shown here is consistent with the expectations reported in the literature for both CMIP3 and CMIP5 models (see for example Seager et al, 2007Seager et al, , 2014Biasutti et al, 2011;Christensen et al, 2013;Maloney et al, 2014). It can be interpreted as the sum of a weak US-wide summertime drying and the wintertime pattern of increase in rainfall north of 40 • N and decrease in precipitation in the southwest and Texas.…”
Section: Erosivity Calculations Using Historical Model Datasupporting
confidence: 91%
See 2 more Smart Citations
“…Although barely significant (see the limited extent of the stippling), there is general drying in Mexico and Texas, extending into the southwest US, and more positive anomalies in the eastern gulf and Florida. The pattern of yearly anomalies shown here is consistent with the expectations reported in the literature for both CMIP3 and CMIP5 models (see for example Seager et al, 2007Seager et al, , 2014Biasutti et al, 2011;Christensen et al, 2013;Maloney et al, 2014). It can be interpreted as the sum of a weak US-wide summertime drying and the wintertime pattern of increase in rainfall north of 40 • N and decrease in precipitation in the southwest and Texas.…”
Section: Erosivity Calculations Using Historical Model Datasupporting
confidence: 91%
“…Areas close to the wintertime zeroanomaly line are areas where the climate signal is projected to be small compared to natural variability, and model disagreement is not problematic. But in other areas, such as northern California and Texas, model disagreement is indicative of true uncertainty in the response (Maloney et al, 2014).…”
Section: Erosivity Calculations Using Historical Model Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Inevitably, as climate changes over North America due to rising greenhouse gases (Maloney et al 2014), the AI will change. This is analyzed in Part II, where we show that models project a general increase in aridity and an eastward movement of the climatically defined 100th meridian (i.e., the longitude where AI ' 1).…”
Section: Variability and Change In The Aridity Index Over 1979 To 2015mentioning
confidence: 99%
“…Based on the most recent climate model projections from phase 5 of the Coupled Model Intercomparison Project (CMIP5) and analyzed by the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5), many workers have reported that North America will see, over the coming decades, a marked transition in hydroclimate. Precipitation is expected to decline in southwestern North America but increase in the northeast, and temperature will rise everywhere (Seager et al 2013;Maloney et al 2014;Seager et al 2014). Cook et al (2015) used the CMIP5 model ensemble to show that these changes combine to cause a quite alarming increase in aridity in the plains as measured either by the Palmer drought severity index (utilizing the Penman-Monteith formulation for potential evapotranspiration) or in the actual modeled soil moisture.…”
Section: Introductionmentioning
confidence: 99%